2022
DOI: 10.25259/sni_1022_2022
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes of vascular clipping in Wistar rats

Abstract: Background: During aneurysm microsurgery, the aneurysmal sac is excluded from circulation by placing one or more clips at the base of the aneurysm. In some cases of complex aneurysms or subarachnoid hemorrhage history, transient clipping before definitive clipping is necessary. The closing force of the transient clip is less than the permanent clip; however, it is sufficient to stop circulation to the aneurysmal sac. The aim of the following work is to analyze and describe histological changes caused by trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…According to the CD68 marker immunohistochemistry results, the protein expressed in monocytes showed no macrophages, which means there had not been an early stage of atherosclerotic lesions [18]. This study showed that one of the earliest defects in e-cigarette seen from histological observations is the elastic fragmentation of the lamina [18][19][20]. Therefore, the absence of CD68positive staining is in fact supporting the evidence that electronic cigarette could have already caused elastic lamina fragmentation even before the early stage of atherosclerotic developed.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…According to the CD68 marker immunohistochemistry results, the protein expressed in monocytes showed no macrophages, which means there had not been an early stage of atherosclerotic lesions [18]. This study showed that one of the earliest defects in e-cigarette seen from histological observations is the elastic fragmentation of the lamina [18][19][20]. Therefore, the absence of CD68positive staining is in fact supporting the evidence that electronic cigarette could have already caused elastic lamina fragmentation even before the early stage of atherosclerotic developed.…”
Section: Discussionsupporting
confidence: 52%
“…The study assessed that someone who smokes and is physically inactive has stiffer blood vessels than those who do not smoke and are physically inactive [ 26 ]. Smoking harms the vascular system, but there was no difference in the vascular stiffness in the active sports group, both smokers and nonsmokers [ 19 , 20 , 26 ]. The difference in our study with the Wistar rat experiment was directly observing the structure that contributes to the stiffness of blood vessels, namely, the elastic lamina.…”
Section: Discussionmentioning
confidence: 99%